Pulsar candidates towards Fermi unassociated sources. Issue 1 (9th June 2016) - Frail, D. A.; Mooley, K. P.; Jagannathan, P.; Intema, H. T.
Abstract: We report on a search for steep spectrum radio sources within the 95 per cent confidence error ellipses of the Fermi unassociated sources from the Large Area Telescope (LAT). Using existing catalogues and the newly released Giant Metrewave Radio Telescope all-sky survey at 150 MHz, we identify compact radio sources that are bright at MHz frequencies but faint or absent at GHz frequencies. Such steep spectrum radio sources are rare and constitute a sample of pulsar candidates, selected independently of period, dispersion measure, interstellar scattering and orbital parameters. We find point-like, steep spectrum candidates towards 11 Fermi sources. Based on the gamma-ray/radio positional coincidence, the rarity of such radio sources, and the properties of the 3FGL sources themselves, we argue that many of these sources could be pulsars. They may have been missed by previous radio periodicity searches due to interstellar propagation effects or because they lie in an unusually tight binary. If this hypothesis is correct, then renewed gamma-ray and radio periodicity searches at the positions of the steep spectrum radio sources may reveal pulsations.